Hydroponic plant education for the community in Tulung District, Klaten Regency - Isnawati, Isnawati; Ratnasari, Dewi; Epianawati, Epa; Ramdani, Dendi; Abdulrohman, Ihsan (Fakultas Kewirausahaan Universitas Garut, 2025)
This community service program aims to improve the capacity of health cadres to support family food security through the understanding and application of hydroponic plant cultivation technology. This activity was carried out in Yogyakarta with participants from Tulung District, Klaten Regency, consisting of health cadres, housewives, and men representing local communities. The activity method included interactive socialization regarding the concept of hydroponics, its benefits for health and food security, and direct practice in building a simple hydroponic system. In addition, the implementation team also provided facilities in the form of hydroponic tools and materials to support the sustainability of the participants' practices in their home areas. The results of the activity showed an increase in participants' knowledge and skills, as well as an emerging interest in developing hydroponic plants as an alternative to utilizing limited land. It is hoped that this activity can be a stimulus in encouraging a healthy and independent community movement through the integration of health, the environment, and household agriculture..